COMPARISON OF THE EFFECTIVINES OF COOPERATIVE LEARNING TWO STAY TWO STRAY AND JIGSAW TYPE WITH SCIENTIFIC APPROACH ON LEARNING MATHEMATICS LEARNING TO GRADE XI MIA AT MAN PANGKEP - Wanna, Wanna (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2016)
The type of this study is experimental research, wich aims at (1) describing the effectiveness of cooperative learning model of Two Stay Two Stray type with scientific approach on Mathematics learnindesg to grade XI MIA at MAN Pangkep, (2) describing the effectiveness of cooperative learning  model of Jigsaw type with scientific approach on Mathematics learning to grade XI MIA at MAN Pangkep, (3) examining whether the cooperative learning model of Jigsaw type is more effective than the Two Stay Two Stray type with scientific approach on Mathematics learning to grade XI MIA at MAN Pangkep. The population of the study is the entire grade XI MIA at MAN Pangkep of academic year 2015/2016. The samples are selected by employing cluster random sampling technique and obtained two classes, namely grade XI MIA 1 taught using the cooperative learning of Two Stay Two Stray type with scientific approach and grade XI MIA 2 taught using the cooperative learning of Jigsaw type with scientific approach. The data collection consists of students’ learning results in Mathematics data, students’ activities data, and students’ response data on the tools and the learning. The results of the study reveal that the students’ learning results in Mathematics of grade XI MIA 1 is in high category with the mean score 76,83 and the standard of deviation is 9.32; the degree of completeness classically is 83.34 %; the mean of normalized gain in fair category, and students’ activities in learning in  good category minimally and students’ responses on the tools and the learning are in positive category. The conclusion of the study is, in general, the cooperative learning model of Two Stay Two Stray type with scientific approach is effective to be applied in grade XI MIA at MAN Pangkep with effective category. The students’ learning results in Mathematics of grade XI MIA 2 is in high category with the mean score 82.65 the standard of deviation is 8.035; the degree of completeness classically is 84.62 %; the mean of normalized gain in fair category, and students’ activities in learning in very good category minimally and the students’ responses on the tools and the learning are in positive category. The conclusion of the study is, in general, the cooperative learning model of Two Stay Two Stray type with scientific approach is effective to be applied in grade XI MIA at MAN Pangkep with effective category. The result of hypothesis test is at the significant level with the t-test indicates that the cooperative learning model of Jigsaw type with scientific approach is more effective than the cooperative learning model of Two Stay Two Stray type with scientific approach in grade XI MIA at MAN Pangkep